Shape Factor for Glass‐Reinforced Plastic Pipes With Noncircular Shapes Under Diametral Loading – An Experimental Study. Issue 4 (7th September 2012) - Seibi, A.C.; Kalfat, I.; Molki, A.; Webb, T.; Flores, R.
<x xml:space="preserve">Abstract</x> An experimental study dealing with testing noncircular glass‐reinforced plastic pipes under compression was conducted. The testing program included four pipe shapes (box, ﬂat elliptic, egg, and round) loaded under the same condition using the parallel‐plate test method. Strain measurements and pipe deﬂections were recorded from which pipe shape factors and stiffness were estimated. The experimental results showed that circular and ﬂat elliptical pipe shapes are, respectively, the stiffest and most ﬂexible ones among all tested pipes. Moreover, the experimental results showed a good agreement with the simulated results of the same tested samples.